High Performance Field Emitters. Issue 5 (18th February 2016) - Collins, Clare M.; Parmee, Richard J.; Milne, William I.; Cole, Matthew T.
Abstract : The field electron emission performance of bulk, 1D, and 2D nanomaterials is here empirically compared in the largest metal‐analysis of its type. No clear trends are noted between the turn‐on electric field and maximum current density as a function of emitter work function, while a more pronounced correlation with the emitters dimensionality is noted. The turn‐on field is found to be twice as large for bulk materials compared to 1D and 2D materials, empirically confirming the wider communities view that high aspect ratios, and highly perturbed surface morphologies allow for enhanced field electron emitters.